Perlindungan Hukum Terhadap Pembajakan Film Melalui Aplikasi Telegram Sebagai Pelanggaran Hak Cipta - Masitoh, Siti (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research was conducted with the aim of examining legal protection for creators of cinematographic films working in wire applications. preparation for robbery, and legal activities for film copyright holders whose work is taken without the right to be distributed by someone via the Wire application. The investigation strategy used is juridical standardization using a statutory approach and a conceptual approach. From the results of this search, it can be seen that until now there are still many haram films circulating in society and there is no awareness among the public and there is no awareness that watching haram films can be a form of violation. The government must take firmer action in checking and blocking these informal or illegal online sites so that the government needs to carry out outreach to the public. Even though there are regulations regarding copyright, violations continue to occur due to weak law enforcement and lack of public awareness. Currently, film piracy on the Telegram application has developed into a big enough problem that it is detrimental to film creators and the film industry as a whole.